2016
DOI: 10.1117/12.2218791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature variations on guided waves propagating in composite structures

Abstract: Effects of temperature on guided waves propagating in composite materials is a well-known problem which has been investigated in many studies. The majority of the studies is focused on effects of high temperature. Understanding the effects of low temperature has major importance in composite structures and components which are operating in cold climate conditions such as e.g. wind turbines operating in cold climate regions. In this study first the effects of temperature variations on guided waves propagating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The variations of temperature affect the propagation of guided waves in laminated composites, as confirmed by the previous studies, [70][71][72][73][74] and the same phenomenon is observed in the current work. The data clusters showing the effect of temperature variation on the healthy state of the composite plate are shown in the red elliptical boundary of Figure 9.…”
Section: Resultssupporting
confidence: 91%
“…The variations of temperature affect the propagation of guided waves in laminated composites, as confirmed by the previous studies, [70][71][72][73][74] and the same phenomenon is observed in the current work. The data clusters showing the effect of temperature variation on the healthy state of the composite plate are shown in the red elliptical boundary of Figure 9.…”
Section: Resultssupporting
confidence: 91%
“…where α and β are the temperature-dependent stretch factors of symmetric and asymmetric wave modes and are obtained by calibrating the model with experimental data. Previous work by the authors described BSS with mode decomposition in detail (Shoja et al, 2016). The method is applied to the results obtained by the FE model in this study in order to handle the effects of temperature on GW propagating in composite structures.…”
Section: Effects Of Temperaturementioning
confidence: 99%
“…In this method, a signal in the time domain is stretched or compressed in such a way that it matches to another signal. Although BSS is a simple method with reasonable accuracy, it is previously shown (Shoja et al, 2016) that the method needs to be modified when it comes to composite materials.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Results verify that BSS with mode decomposition (MD) shows slightly better performance than BSS with one stretch factor. 26 Despite numerous methodologies in literature, however, it has been summarized that it is not possible to completely manipulate the effect of temperature in SHM, and there is still need of further improvements and authentic model to identify and estimate the thermal sensitivity of ultrasonic guided waves. Therefore, the interpretation of temperature effect on the guided wave propagation in real-time practical inspections through an authentic model is necessary to achieve optimum results.…”
Section: Introductionmentioning
confidence: 99%